1982
DOI: 10.1099/0022-1317-61-1-15
|View full text |Cite
|
Sign up to set email alerts
|

Protein Synthesis in HeLa Cells Double-infected with Encephalomyocarditis Virus and Poliovirus

Abstract: SUMMARYThe pattern of host, encephalomyocarditis (EMC) virus and poliovirus protein synthesis in HeLa cells double-infected with EMC virus and poliovirus has been examined. Both picornaviruses were able to block host translation after infection, although with different degrees of efficiency. In co-infection experiments, the inhibition of poliovirus protein synthesis by EMC virus and vice versa depended on the relative multiplicities of infection of each virus used. Under some conditions, double-infected HeLa c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1982
1982
1995
1995

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…DitTerential inhibition by poliovirus ZAP'" of vaccinia virus expression and poliovirus protein 2C production. Translation of poliovirus mRNA occurs after p23-0 cleavage in infected cells (Sonenberg, 1990) and translation or poliovirus and encephalomiocarditis vinis (EMC) virus mRNhs occurs in doubly infected cells (Alonso and Carrasco, 1982). Thcse results indicate that inract p220 is not necessary for internal translational initiation of these mRNAs. '…”
Section: Resultsmentioning
confidence: 99%
“…DitTerential inhibition by poliovirus ZAP'" of vaccinia virus expression and poliovirus protein 2C production. Translation of poliovirus mRNA occurs after p23-0 cleavage in infected cells (Sonenberg, 1990) and translation or poliovirus and encephalomiocarditis vinis (EMC) virus mRNhs occurs in doubly infected cells (Alonso and Carrasco, 1982). Thcse results indicate that inract p220 is not necessary for internal translational initiation of these mRNAs. '…”
Section: Resultsmentioning
confidence: 99%
“…Carrasco has suggested that the increased permeability of virusinfected cells to monovalent cations might mediate the switch from host to viral translation (Carrasco and Lacal, 1983;Carrasco and Smith, 1976). When infected cells are incubated in medium containing sufficient excess NaCl to inhibit the translation of most other proteins, poliovirus translation is fairly resistant (Alonso and Carrasco, 1982a;Nuss et al, 19751, but the resistance is not as striking as with EMC virus (Alonso and Carrasco, 1982b). The stimulation of in uitro translation by high salt is also less obvious with poliovirus mRNA than with some other picornaviruses (Bossart and Bienz, 1981).…”
Section: Other Considerationsmentioning
confidence: 99%
“…In the natural course of infection by poliovirus, the precipitous decline in host translation occurs within the first 2 hours, prior to the observed increase in intracellular sodium ions (Nair et al, 1979). Moreover, the synthesis of cellular proteins cannot be reactivated by incubating poliovirusinfected cells in hypotonic medium (Alonso and Carrasco, 1982b), a manipulation that works beautifully with EMC virus. Thus, hypertonicity does not appear to underlie the shutoff of host protein synthesis by poliovirus.…”
Section: Other Considerationsmentioning
confidence: 99%
“…Even the translation of another picornavirus RNA, such as EMCV RNA, is efficiently blocked by poliovirus when similar multiplicities of infection are used (Alonso & Carrasco, 1982b), indicating that the poliovirus-induced inhibition L. Pgrez, A. Irurzun and L. Carrasco of EMCV mRNA translation is possibly not mediated by the blockage of cap recognition factors. Under some conditions, particularly when low poliovirus m.o.i.s are used, translation of other viral mRNAs, including capped mRNAs, occurs in poliovirus-infected cells (Schrader & Westaway, 1990;Mufioz et al, 1984Mufioz et al, , 1985Alonso & Carrasco, 1982a).…”
Section: Introductionmentioning
confidence: 97%